1992
DOI: 10.4294/jpe1952.40.617
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Structure of the Hypocenter Distributions and Focal Mechanism Solutions of Acoustic Emission in Two Granites of Different Grain Sizes.

Abstract: Coarse-grained Inada granite (grain size 5 mm in average) and fine-grained Oshima granite (grain size < 2 mm) samples were deformed in triaxial compression experiments. Acoustic emission (AE) was monitored using 20 transducers in real time. In each experiment, hypocenters of some thousands of events were determined using anisotropic velocity model based on measured data. The spatial distributions of AE hypocenters in both rocks had fractal structure. Their fractal dimensions were 2.3 and 2.7 in average for Ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 19 publications
4
56
1
Order By: Relevance
“…During propagation of compaction bands S-and C-type events represent about 24% and 72% of the source mechanisms, respectively, and tensile cracks represent less than 4%. The observations are in agreement with other studies [16,[25][26].…”
Section: Discussionsupporting
confidence: 94%
“…During propagation of compaction bands S-and C-type events represent about 24% and 72% of the source mechanisms, respectively, and tensile cracks represent less than 4%. The observations are in agreement with other studies [16,[25][26].…”
Section: Discussionsupporting
confidence: 94%
“…Zhao 1998) or optical microscopy (Wong 1985;Cox and Scholz 1988) operated during or after a fracture test, and (2) monitoring of the spatiotemporal distribution of AE events caused by microcracking activity (e.g. Lockner et al 1991;Lei et al 1992), which is the so-called AE technique. Fracturing dynamics and the pre-failure damage can be inferred from AE statistics as the number of AE events is proportional to the number of growing cracks, and the AE amplitudes are proportional to the length of crack growth increments in the rock (e.g.…”
Section: Ae As An Analogue Model Of Earthquakesmentioning
confidence: 99%
“…Such heterogeneities are characterised by fractal self-similarity or hierarchical structures (e.g. Ouillon et al 1996;Lei et al 1992). As a result, the fractures in the crust are somehow governed by the heterogeneities they involve.…”
Section: Introductionmentioning
confidence: 99%
“…Hasegawa and Tanemura (1986) reviewed statistical methods that can measure the distance between the observed distribution and various modeled statistical distributions. Nishizawa (1992) applied one of these methods (the two-body correlation function method) to the distribution of AE hypocenters in a granite sample during creep under 40MPa confining pressure and demonstrated that the L-statistic can express the detailed structure of the distribution (for further information about the method, see Besag, 1977).…”
Section: Stochastic Characters Of Ae Hypocenter Distributionmentioning
confidence: 99%